Technologies applied to the recovery of bioactive compounds from food fluids and their performance in the biosynthesis of nanometals: a case study with Morinda citrifolia - Almeida, Édipo da Silva (2022)
Tese (doutorado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia de Alimentos, Florianópolis, 2022.